Bioaccumulation of some metals by Green mussel Perna viridis (Linnaeus 1758) from Pekan, Pahang, Malaysia - Yunus, Kamaruzzaman; Md Suhaimi, Mohd Zahir; John, Akbar; Khan Chowdhury, Ahmed Jalal; Saad, Shahbudin; Al-Barwani, Said Mohd; Goddard, J Stephen (Academic Journals Inc., USA, 2011)
A study was conducted to determine the bioaccumulation of some essential and non-essential heavy metals by the soft tissue of Perna viridis (Green mussel) collected from Pekan, Pahang during November 2009. A total of fifty individuals of Green lipped mussel P. viridis (Family: Mytilidae) were sampled and metals such as Iron (Fe), Zinc (Zn), Copper (Cu), Cobalt (Co), Lead (Pb) and Cadmium (Cd) concentration were determined using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The observed mean concentration of Fe, Zn, Cu, Co, Pb and Cd in the soft edible tissue of P. viridis was 576.45±87.78, 45.54±8.75, 19.05±4.12, 17.85±2.28, 0.47±0.14 and 0.3±0.06 μg g-1, respectively. The bioaccumulation of metals in the soft tissue flowed in Fe>Zn>Cu >Co>Pb>Cd order indicating that the essential heavy metal accumulates in faster rate than non-essential metals. Comparison with earlier studies showed that Fe and Cu bioaccumulation level was higher in samples from Pekan area with average of 576.45 and 19.05 μg g-1, respectively. All the other metals concentration was lower in the soft tissue of green mussel indicating comparatively lower heavy metal contamination in the Pekan, Pahang compared with other coasts.